Experimental investigation and process optimization of the ultrasonic welding applied to papers. Issue 8 (16th August 2021) - Charlier, Q.; Viguié, J.; Harthong, B.; Toni, J.‐B.; Terrien, M.; Imbault, D.; Peyroux, R.
Abstract: Ultrasonic welding is a serious candidate in the development of methods to assemble papers and paperboards without using additional substances. However, the ultrasonic welding of papers remains a technological challenge considering the low weldability of lignocellulosic materials. This study aims to investigate on the ultrasonic welding process applied to papers in order to identify the processing conditions which favor the formation of strong welded joints. To reach such purpose, an experimental strategy was developed by combining the characterization of welded materials and the monitoring of process parameters. Experimentations were performed using a reference paper displaying a good weldability to specifically highlight the contribution of process parameters. Results indicate that the process is highly sensitive to vibration amplitude, power supplied by the high frequency generator, and sample thickness. Power seems to be a reliable indicator of the severity of the process. A strong decrease in the strength of the welded joints is observed when working with low thicknesses. It seems that the layers coated on top of papers are the main part of the material contributing in the development of adhesion at the welding joint. Overall, instrumenting the device has led to a better understanding of the ultrasonic welding of papers. Abstract : Ultrasonic welding can be used to assemble papers and paperboards without using additional substances. The stakes are high as it could lead to the development of 100 % bio‐based and recyclable packaging solutions. But it remains a technological challenge considering the low weldability of lignocellulosic materials. What are the processing conditions favoring the formation of strong welded joints?